MANAJEMEN RISIKO FINTECH DALAM PEMBIAYAAN SYARIAH - Darmawan Darmawan; Muh. Taufiq Al Hidayah (Business Journal : Jurnal Bisnis Dan Sosial, 2019)
In the limited access to finance, financing alternatives began to emerge. This is marked by the presence of information technology-based providers of services called Financial Technology. In addition to financing, Fintech companies in Indonesia also have various convenience services ranging from payments, financial planning, financial research, and others. Credit risk that often occurs is the failure of returning some of the financing provided and becoming non-performing loans that affect the bank's income and operations. Fintech with the P2P Landing scheme, will have a higher risk of financing problems, because it does not allow checking the track record of prospective borrowers, not directly face to face. PT. Indves Dana Syariah is one of the Fintech companies that also uses P2P Landing schemes. PT. IDS is one of the many Fintech Sharia that are operating in Indonesia using syariah contracts such as musharaka and mudharabah. PT. IDS was chosen because it is one of the FinTech sharia pioneers in Indonesia and also has a Sharia Supervisory Board. This study aims to find out what are the risks faced by PT. IDS in channeling Sharia Business Financing? And how is the financing risk management strategy conducted by PT. IDS? This study included field research using qualitative descriptive approaches. Researchers used the Miles and Huberman models in analyzing the data collected. The results of this study indicate that: Fintech with the P2P Landing Scheme used in Sharia Business Financing has various risks. Besides the risks that are generally the same as banking, the biggest risk is failure to pay. This risk is a priority risk that must be managed in order to gain creditor trust. In addition, it also has Cybersecurity risk and debtor data misuse; and Risk Management carried out in suppressing financing with credit scoring used: Social Media Networking Analysis and Big Data. The success of this risk management method is indicated by the absence of bad financing in this Sharia Business Financing.